Corporal Punishment: Law Reform Lessons for Australia from South Africa and New Zealand - Greeff, Laetitia-Ann (Comparative and International Law Journal of Southern Africa, 2021)
This article compares the law reform methods employed by South Africa and New Zealand to eliminate the defence of ‘moderate and reasonable chastisement’ to a charge of common assault, to determine the best possible law reform strategy for Australian jurisdictions, within the context of its federal system of governance. South Africa and New Zealand banned corporal punishment on a national level, with South Africa prohibiting the use of corporal punishment by way of the judicial condemnation of the Constitutional Court in 2019, and New Zealand’s legislation to ban corporal punishment through Parliamentary processes in 2007. Corporal punishment in the home is still legal in Australia if administered by parents or those in loco parentis. This article focuses on the three Australian States that have enacted human rights legislation—Victoria, the Australian Capital Territory (ACT) and Queensland—and the impact of this legislation on judicial law reform. In this regard, the doctrine of parliamentary sovereignty is discussed in terms of its ability to limit public interest litigation’s viability to strike down inconsistent legislation. The article suggests that all three countries can learn from one another concerning the successes and/or failures of law reform. Furthermore, the article concludes by acknowledging that even though formal abolition is the norm in South Africa and New Zealand, corporal punishment remains widespread. Parents and those in loco parentis must be supported by continual education initiatives to bring about requisite social and cultural change.